The interrelationship among critical thinking, writing an argumentative essay in an L2 and their subskills. Issue 4 (2nd October 2017) - Soodmand Afshar, Hassan; Movassagh, Hossein; Radi Arbabi, Hassan
Abstract : This study investigated the relationship between critical thinking and the writing ability of Iranian EFL learners, and the interrelationship among the subskills of the two constructs. Furthermore, it aimed at finding which skills of critical thinking predicted the participants' writing ability. To this end, 104 students majoring in English Language took the California Critical Thinking Skills Test and the Writing section of the IELTS test which required them to develop a piece of argumentative writing. Their writings were scored by two experts against the four subskills dictated by the IELTS test rubrics. The results indicated a significant correlation between critical thinking and writing ability of the participants. Moreover, among the subskills of writing ability, only organisation was correlated with certain subskills of critical thinking. The results of multiple regression analysis revealed that among the five components of critical thinking, analysis and evaluation turned out to be stronger predictors of writing ability.